SISTEM PENDUKUNG KEPUTUSAN ALTERNATIF PEMELIHARAAN BANGUNAN GEDUNG DI POLITEKNIK NEGERI SRIWIJAYA - Sudarmadji Sudarmadji (PILAR, 2011)
Maintenance system for buildings at Politeknik Negeri Sriwijaya has been running Standard Operational Procedure (SOP) which made by Subag Tata Usaha, but the targets are not optimal, there are still many buildings maintenance actions that have not been in accordance with the purposes of the conditions in the field. The problem is caused by the absence of data base and decision support systems maintenance building alternative that can store, access, update and make decisions properly and correctly, so common maintenance activities that have been done are often not recorded and it is difficult to know the history of data events maintenance in the past, and the consequences, the decision making to determine the alternative maintenance and treatment is often not appropriate.The purpose of this study is to make alternative maintenance decision support system to determine the alternative priority of building maintenance based on “building condition index” and deviation of condition index divided by the cost of maintenance for effective use of budgets and create your simple database model that can be used to help access, preserve and renew building maintenance data. Early step of object in this research is the object of Phase I Building in Politeknik Negeri Sriwijaya; there are Gedung Kuliah Sipil, Gedung Laborarorium and Bengkel Sipil, Gedung Kuliah Mesin, Gedung Laboratorium Mesin and Gedung Bengkel Mesin. The weighting system use multi-criteria theory of Analytic Hierarchy Process (AHP) with the help from  Expert Choice Software.The results stated Door Sub Component has the lowest Condition Index value, it is 91,7%, and on the Room Function, Support Room, the Condition Index value is 95,4%, is the first priority in terms of handling damage, followed by Theory Room and Office / Staff Room. So, the general condition of Gedung Kuliah Sipil Building Phase 1 Politeknik Negeri Sriwijaya is good, while the maintenance priorities based on the comparison of Δ Condition Index / required maintenance fee, Sub Component of Doors with comparison value 2,594 x 10-7  is the first priority and based on room function, Library Room is first priority with comparison value 1,647 × 10-8.